2008
DOI: 10.1097/hjh.0b013e32830bfdd9
|View full text |Cite
|
Sign up to set email alerts
|

Menopause does not affect blood pressure and risk profile, and menopausal women do not become similar to men

Abstract: The cardiovascular effects usually attributed to menopause seem to be a mere consequence of the older age of menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 74 publications
3
41
0
5
Order By: Relevance
“…Casiglia et al 35 , in a study with 9,364 Italian men and women found results that were similar to the ones of this study: higher prevalence of MS components among postmenopausal women, but this difference disappeared after adjustment for age. In the study conclusion, the authors mentioned that "the cardiovascular effects usually attributed to menopause seem to be merely a consequence of the older age of menopausal women 35 .…”
Section: Figueiredo Neto Et Al Metabolic Syndrome and Menopausesupporting
confidence: 72%
See 1 more Smart Citation
“…Casiglia et al 35 , in a study with 9,364 Italian men and women found results that were similar to the ones of this study: higher prevalence of MS components among postmenopausal women, but this difference disappeared after adjustment for age. In the study conclusion, the authors mentioned that "the cardiovascular effects usually attributed to menopause seem to be merely a consequence of the older age of menopausal women 35 .…”
Section: Figueiredo Neto Et Al Metabolic Syndrome and Menopausesupporting
confidence: 72%
“…In the study conclusion, the authors mentioned that "the cardiovascular effects usually attributed to menopause seem to be merely a consequence of the older age of menopausal women 35 . "…”
Section: Figueiredo Neto Et Al Metabolic Syndrome and Menopausementioning
confidence: 99%
“…The gender differences may be related to the faster transport of lipids in the bloodstream of women compared with men in the blood stream, earlier age-graded serum cholesterol changes in women, and higher concentrations of cholesterol in elderly women than men (53)(54)(55). However, our results underscored the importance of keeping cholesterol concentration within the high normal range, although a longitudinal follow-up is needed to determine whether higher cholesterol prevents later life cognitive impairment in both men and women.…”
Section: Discussionmentioning
confidence: 99%
“…20 In older women, menopause might contribute to the continuing rise in SBP, although it is difficult to differentiate the effects of aging from those of estrogen deprivation. 21,22 Single regression co-efficients (b ± s.e.) describe the cross-sectional associations of blood pressure with age.…”
Section: Discussionmentioning
confidence: 99%